2020
DOI: 10.24171/j.phrp.2020.11.4.09
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoking Among Children in Rural Households: A Community Based Cross-Sectional Study in Bangladesh

Abstract: This study aimed to determine the factors associated with reducing exposure to secondhand smoke among children in households of rural Bangladesh. Methods: A cross-sectional study of 410 smokers and non-smokers, in 6 villages of Munshigonj district was conducted. Data were collected randomly using a self-administrative questionnaire. Differences between variables were assessed using Chi-square or Fisher's exact test (as appropriate). Univariate and multivariate logistic regression models were used to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…The result also was in line with another study in Canada among young adults 17 . Our study showed woman empowerment as a significant factor in line with other studies conducted in South Asia 16 , 18 . Smoking in a visible place increases a non-smoker’s chances to start smoking and increasing SHS, which was also found in a study conducted in England 19 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The result also was in line with another study in Canada among young adults 17 . Our study showed woman empowerment as a significant factor in line with other studies conducted in South Asia 16 , 18 . Smoking in a visible place increases a non-smoker’s chances to start smoking and increasing SHS, which was also found in a study conducted in England 19 .…”
Section: Discussionsupporting
confidence: 92%
“…The result also was in line with another study in Canada among young adults 17 . Our study showed woman empowerment as a significant factor in line with other studies conducted in South Asia 16,18 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Drawing upon prior work [ 36 38 ] and a relevant systematic review and thematic synthesis [ 39 ], a semi-structured interview schedule that explored smoking behaviours, and barriers and facilitators to an SFH intervention delivered within mosques by Imams was developed. Given the aforementioned process evaluation [ 24 ] had identified issues around the acceptability and feasibility of the use of mosques to disseminate SHS messages, we took this opportunity to elicit opinions on this.…”
Section: Methodsmentioning
confidence: 99%
“…Bangladesh is reported to have a high prevalence of exposure to secondhand smoke (SHS) due to the cheap cost and accessibility of cigarettes 23 , 24 . In Bangladesh, the prevalence of secondhand smoking was found to be 39.1% for adults and 31.1% for children aged 13 to 15 in earlier studies conducted in 2013 and 2017 23 , 25 , 26 . In addition, the prevalence of smoking among university students in Bangladesh is 60.2%, thus, increasing the likelihood of exposure to SHS 27 .…”
Section: Introductionmentioning
confidence: 99%